The magnetic resonance shutter speed discriminates vascular properties of malignant and benign breast tumors in vivo - Huang, Wei (National Academy of Sciences, 2008)
The pharmacokinetic analysis of dynamic-contrast-enhanced (DCE) MRI data yields K(trans) and k(ep), two parameters independently measuring the capillary wall contrast reagent transfer rate. The almost universally used standard model (SM) embeds the implicit assumption that equilibrium transcytolemmal water exchange is effectively infinitely fast. In analyses of routine DCE-MRI data from 22 patients with suspicious breast lesions initially ruled positive by institutional screening protocols, the SM K(trans) values for benign and malignant lesions exhibit considerable overlap. A form of the shutter-speed model (SSM), which allows for finite exchange kinetics, agrees with the SM K(trans) value for each of the 15 benign lesions. However, it reveals that the SM underestimates K(trans) for each of the seven malignant tumors in this population. The fact that this phenomenon is unique to malignant tumors allows their complete discrimination from the benign lesions, as validated by comparison with gold-standard pathology analyses of subsequent biopsy tissue samples. Likewise, the SM overestimates k(ep), particularly for the benign tumors. Thus, incorporation of the SSM into the screening protocols would have precluded all 68% of the biopsy/pathology procedures that yielded benign findings. The SM/SSM difference is well understood from molecular first principles.